2024
DOI: 10.1002/acr.25245
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Severity, and Measures of Anxiety in Rheumatoid Arthritis: A Systematic Review

Tanya Meade,
Caroline Joyce,
Tania Perich
et al.

Abstract: ObjectivesMany studies have reported high rates of anxiety in adults with Rheumatoid Arthritis (RA). The aim of this systematic review was to examine those findings and determine the overall prevalence, severity, and commonly used measures of anxiety in individuals with RA.MethodsSix databases were searched from January 2000 without restrictions on language/location, study design, or grey literature. All identified studies that examined anxiety prevalence and severity in adults with RA, as assessed with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…Numerous studies have reported an association between RA and depression [53][54][55]. One similar study in Germany reported the prevalence of depression in RA patients as 32% [39], while another study with a different age sample and definition of depression reported a prevalence of 15% to 39% [56]. This difference could be caused by the difference in observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported an association between RA and depression [53][54][55]. One similar study in Germany reported the prevalence of depression in RA patients as 32% [39], while another study with a different age sample and definition of depression reported a prevalence of 15% to 39% [56]. This difference could be caused by the difference in observation period.…”
Section: Discussionmentioning
confidence: 99%